2016
DOI: 10.1002/jor.23237
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical characteristics of pedicle screws in osteoporotic vertebrae—comparing a new cadaver corpectomy model and pure pull‐out testing

Abstract: Currently, evaluation of the stability of spinal instrumentations often focuses on simple pull-out or cyclic loading. However, the loading characteristics and the specimen alignment rarely simulate physiological loading conditions, or the clinical situation itself. The purpose of this study was to develop an alternative setup and parameters to compare static and dynamic characteristics of pedicle screws at the bone-implant interface in lumbar osteoporotic cadavers. A corpectomy model development was based on A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
2
17
0
1
Order By: Relevance
“…Numerous biomechanical studies in vitro have attempted to clarify crucial factors for the anchorage capacity of pedicle screws, focusing on bone density, insertion depth, misplacement, and insertion angle. However, these studies have inherent limitations associated with a cadaveric study and/or bone models, in which it is difficult to mimic the actual clinical situation, such as the influence of adjacent vertebral musculature and ligaments, and the wide variations in the material properties of bone, living tissues, and postoperative loading [4][5][6]9,[16][17][18][19][20][21][22] . Therefore, the strengths and clinical relevance of this study are that it showed that a lower axial trajectory and a high screw pull-out force during rod connection might be crucial risk factors for PPS loosening in clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous biomechanical studies in vitro have attempted to clarify crucial factors for the anchorage capacity of pedicle screws, focusing on bone density, insertion depth, misplacement, and insertion angle. However, these studies have inherent limitations associated with a cadaveric study and/or bone models, in which it is difficult to mimic the actual clinical situation, such as the influence of adjacent vertebral musculature and ligaments, and the wide variations in the material properties of bone, living tissues, and postoperative loading [4][5][6]9,[16][17][18][19][20][21][22] . Therefore, the strengths and clinical relevance of this study are that it showed that a lower axial trajectory and a high screw pull-out force during rod connection might be crucial risk factors for PPS loosening in clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…As reported elsewhere, we developed a method to apply quasi-physiological loading and detect screw movement [11]. To our knowledge, the effect of cement augmentation in an in vivo physiological setup focusing on the observed screw movement has not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, they were not able to draw this conclusion based on a cyclic fatigue test, which is a more physiological testing method for screw failure testing [23,30]. especially since withdrawing of the screws posteriorly through the pedicle has clinically rarely been reported [12,23,27,31].…”
Section: Discussionmentioning
confidence: 98%